Portugal’s resistance to decolonization and the “White Redoubt” (1950–1974) - Barroso, L. (Oxford research encyclopedia of African history, 2020)
Portugal’s resistance to decolonization lasted from the mid-1950s until the fall of the regime in April 1974, and it helps to explain why Portugal fought thirteen years of war in Angola, Mozambique, and Guinea. Contrary to other colonial powers, the Portuguese rulers were not willing to accept the winds of change nor to meet the demands for the self-determination of its overseas territories that had swept Africa and Asia from the early 1950s. Several factors can explain the inflexibility of Lisbon to accept them, ranging from the ideological nature of the New State; from the strategic context of the Cold War due to the importance of the Azores islands for the United States and NATO; or from Portugal’s alliance with Great Britain. When the war broke out in Angola, and the Indian Union seized the “Portuguese India” territories in 1961, prime-minister Salazar did not receive the political support he expected from Washington and London as traditional allies. In early 1962, Salazar decided to strengthen relations with South Africa and Rhodesia in an attempt to maintain white rule in its overseas territories amidst a drive for independence by African nationalists, so-called “white redoubt,” that was the terminology used by the Kennedy administration to refer to the set of African countries and territories dominated by white minority governments: Angola, Mozambique, Southern Rhodesia and South Africa. Strengthened ties would aid his strategy to keep the war effort in Africa by taking advantage of the importance of Angola and Mozambique to the security of South Africa. In 1964, Salazar encouraged Ian Smith to unilaterally declare independence from Great Britain to link Angola and Mozambique to the Southern Africa Security Complex led by South Africa, despite widespread criticism of the apartheid in the United Nations (UN). Concurrently, Lisbon tried to seduce Hastings Banda and Kenneth Kaunda in expelling the liberation movements from Malawi and Zambia in exchange for granting transit facilities to ease the international pressure with regards to its colonial policy. Following several years of military collaboration, in October 1970, Portugal, South Africa, and Rhodesia established a military alliance codenamed “Exercise ALCORA,” which aimed to coordinate the global efforts against the insurgency in Southern Africa. Portugal used the ALCORA to obtain substantial aid in the form of military equipment and financial support, which Portugal needed to keep the war effort in the three African territories. In early 1974, Caetano channeled the South African loan to prevent a significant setback in Guinea, because if it were lost, Mozambique and Angola would follow, and consequently the regime.